A mediastinal false aneurysm with aortocutaneous fistula - (:unkn) unknown (FORUM MULTIMEDIA PUBLISHING, LLC, 2004)
In this report, we present a case of the development of a false aneurysm of the ascending aorta with an aortocutaneous fistula in a 57-year-old patient 10 months following aortic valve replacement and concomitant coronary bypass surgery.
Keywords: ASCENDING AORTA; GRAFT REPLACEMENT; SURGERY